Hydraulic Tomography and Trichloroethene Dissolution in a Fractured Dolostone: Small Scale Laboratory Experiments - Sharmeen, Rubaiat (University of Waterloo, 2011)
In fractured geologic media, flow and contaminant transport are predominantly controlled by the fractures, their distribution and connectivity. The accurate characterization of fractured geologic medium, imaging of fracture patterns and their connectivity have been a challenge for decades. Given the complexities of fractured networks in the subsurface and Dense Non Aqueous Phase Liquid (DNAPL) contamination, in this thesis, transient hydraulic tomography (THT), a recently developed tool for characterizing aquifer heterogeneity is evaluated under laboratory conditions to delineate discrete fractures. Laboratory experiments and modeling studies are also conducted to understand TCE plume behavior. A dolomite rock sample, which is 91.5 cm in length, 60.5 cm in height and 5 cm thick, was fractured in the laboratory to perform the experiments. After the fractured block was enclosed in a flow cell, flow-through and pumping tests were conducted to characterize the fractured rock block. The data from the pumping tests were then analyzed using the SSLE code developed by Zhu and Yeh [2005] and transient hydraulic tomography (THT) was conducted to image the fracture pattern and their connectivity through the delineation of K and Ss distributions (the tomograms). Synthetic pumping tests, identical in configuration to the laboratory ones were also conducted using HydroGeoSphere (HGS) [Therrien et al, 2009] in a synthetic replica of the fractured block to compare the observed and simulated drawdowns. Then synthetic THT analysis was performed utilizing the synthetic pumping test data to compare the tomograms obtained from the THT analysis of synthetic and laboratory pumping tests. Results suggest that the THT analysis of multiple laboratory pumping tests captured the fracture pattern and their connectivity quite well and they became more vivid with the additional pumping tests. The estimated high hydraulic conductivity (K) and low specific storage (Ss) zones clearly show the fractures and their connectivity. The pattern of K and Ss tomograms obtained from the analyses of synthetic and laboratory pumping tests were similar. Estimated K and Ss values for the fractures and the matrix may not exactly replicate the actual K and Ss values for the fractured rock, but the model also provides uncertainty estimates associated with the resulting K and Ss tomograms. In this study, two cases of transient hydraulic tomography (THT) analysis of the laboratory pumping tests were performed by changing the location of 2nd and 3rd pumping tests among the three to examine if there is any significant impact of these pumped location on the pattern of resulting hydraulic conductivity (K) and specific storage (Ss). The initial pumping test was the same for two cases. Results show that the patterns of estimated K and Ss tomograms obtained from these two cases are similar, although the pumped locations (2nd and 3rd tests among the three) utilized for the inversion were different for two cases suggesting that the location of these later pumping tests does not significantly impact the estimates for this fractured rock block. However, the initial test should be selected carefully as that seems to set the pattern of the tomograms. The estimated K and Ss tomograms were validated by predicting five independent pumping tests conducted in the fractured rock block. These five pumping tests were not included during the construction of the K and Ss tomograms. For most of the independent pumping tests, good correspondence between the simulated and observed drawdown was achieved. The study indicates that, it is possible to delineate discrete fractures, their pattern and connectivity by carefully applying of THT analysis of multiple pumping tests based on the inverse code SSLE [Zhu and Yeh, 2005]. In addition, hydraulic tomography seems to be a cost effective tool for characterizing fractured rock since it does not require the detailed information on fracture geometry parameters such as aperture, trace length, orientation, spatial distribution, and connectivity, which are difficult to quantify. These parameters are usually unavailable between boreholes. Therefore, THT appears to be a promising approach in delineating fractures and their connectivity in subsurface. However, it is still at the early stage as the study was conducted in the laboratory under controlled conditions. Small scale field experiments need to be conducted to validate THT as a tool for the characterization of hydraulic parameters of fractured rocks. Upon completion of the hydraulic characterization, several conservative tracer tests were conducted using bromide (Br-) as a conservative tracer to aid in the design of TCE dissolution experiment. Once the tracer experiments were completed, a known volume of pure phase TCE was injected at a known location in the flow cell to create a well-defined source zone. A constant hydraulic gradient was maintained by fixing the hydraulic heads at the two head tanks to induce steady groundwater flow through the flow cell. Water samples were obtained at a down gradient monitoring port for 3 months to obtain a long-term breakthrough curve of TCE in the aqueous phase. The purpose of this experiment was to study TCE dissolution behaviour in the fractured rock sample. Then HydroGeoSphere (HGS) was used to model the aqueous phase TCE transport using two separate approaches: 1) the Discrete Fracture Network modeling approach and 2) the stochastic continuum approach, to investigate whether they can capture the dissolution behavior. Both approaches were able to capture the pattern of the breakthrough curve in the fractured rock. The discrete fracture approach captured the observed TCE plume and the dissolution behavior quite well. On the other hand, the stochastic continuum approach, in which the fractured rock block was treated as porous medium having a heterogeneous K field obtained from THT analysis, also appeared to be promising in capturing the aqueous phase transport of TCE. Despite some early time deviation, the simulated breakthrough curve captured the overall observed concentration profile. However, the stochastic continuum approach seems to be more cost effective as it does not require detailed information about fracture aperture and their spatial distribution which are difficult if not impossible to obtain between boreholes. Note that, the studies were conducted based on a laboratory experiment conducted in a controlled environment. The experimental block was well characterized and the geometry of the experimental block as well as the flow through the system was well understood from the hydraulic and tracer experiments. Thus small scale field experiment is required to support this conclusion.
Keywords: Groundwater; Experiment; Modeling; Fractured Rock; Earth Sciences